Fluktuace a vztahy s veřejností - Kupec, Václav (Communication Today, 2025)
The paper deals with connections between the fluctuation rate and public relations and the aim is to analyze them thoroughly. After the preliminary theoretical analysis of these problems and with contribution of knowledge not only from the field of management, psychology, personnel management and marketing, the main interest lies in fulfilling the setting. That is to record concrete facts which take place in relationship chain: management, employees and external environment, with the help of specialized methods intended for observing of ongoing in-house processes in the company. The collated information were summarized and presented as the results of this study, adverting to definite interconnection between fluctuation and relationships with public. To be specific, the results explain the processes where employees and their loyalty to their employers might be one of the main communication channels in PR companies. Moreover, in practice, the described findings have fundamental influence on final economic achievement of particular companies. In its conclusion, the article offers a recommendation showing the necessity to use appropriate management access when dealing with these problems, because the fluctuation rate goes far beyond the internal environment of the company.